Study of wear properties of Aluminum Alloy 332 at difference sliding distance - Zainon Fizam, Daud Ruslizam, Ahmad Khairel Rafezi (Universiti Pendidikan Sultan Idris, 2016)
Study of wear properties of Aluminum Alloy 332 at difference sliding distance by Zainon Fizam, Daud Ruslizam, Ahmad Khairel Rafezi,